The media ideologies of medical influencers:: Between distrust of social media strategies and management of follower expectations - Ieracitano, Francesca; Centola, Alessia (Mediascapes journal, 2025)
This study compares the media ideologies of Italian med-influencers and their followers concerning medical personal branding on social media. The existing literature explores how medical practitioners promote themselves online. Nevertheless, it overlooks the beliefs shaping how med-influencers use social media for personal branding and how they perceive their followers’ expectations. In order to explore med-influencers and followers’ media ideologies, 30 semi-structured interviews, integrated with the techniques of cognitive walkthrough and thinking aloud methods, were carried out. The interviews with the Italian med-influencers and followers were analyzed through a thematic analysis. The results reveal a lack of awareness of social media logic among med-influencers, a deterministic approach towards social media, and false beliefs about follower expectations. These media ideologies affect the choice of med-personal branding strategies, limiting them to clarity, entertainment, and the sharing of personal content. Med-influencers believe that posting personal and fun content is enough to humanize the doctor’s role. Conversely, followers prioritize genuine emotional engagement. Findings suggest that, while digital literacy skills are important, med-influencers also need greater awareness of how their beliefs and misconceptions may affect personal branding practices.